Food choice behavior of adolescents under parent-child interaction in the context of US school lunch programs. (February 2023) - Panchalingam, Thadchaigeni; Howard, Gregory; Allen Klaiber, H.; Roe, Brian E.
Highlights: Both parents and students value the local sourcing of school meals in the U.S. Parent and student preferences for locally sourced foods are not always identical. Parents drive the additional value placed upon locally produced vegetables. Abstract: A relatively new trend in school feeding programs around the world is procuring food from local producers. However, little is known about student preferences for locally sourced food in school meals and how the interaction between parent and student preferences for locally sourced items influence joint school lunch decisions. We conducted a nationwide survey in the U.S. that embeds a school lunch discrete choice experiment. Results indicate that students and parents would prefer that locally produced items be added to school lunch menus. However, while parent and student preferences align on some aspects of locally sourced meal elements, their preferences are not identical, with parents displaying a higher willingness to pay for locally sourced vegetables and students displaying a higher willingness to pay for locally sourced fruit. Joint choices are influenced by both parties. Parents dominate the joint outcomes when the household income is lower, when students eat school lunch more frequently and in dyads featuring a female parent and female student compared to male parent-male student dyads. Our findings emphasize why analyzing joint parent-student food choice behavior, rather than individual choices, is vital to understand participation in school feeding programs and hold implications for efforts to promote locally sourced food elements in school meals and the role of parent engagement in that process.